Uncovering the hidden cost of staff fraud: an assessment of 45 cases in the UK. Issue 2 (5th May 2015) - Button, Mark; Blackbourn, Dean; Lewis, Chris; Shepherd, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide evidence on the additional costs of dealing with staff fraud, beyond the initial fraud loss, based on 45 cases of staff fraud. Design/methodology/approach – The research began with a "brainstorming" session with counter fraud professionals to map all potential costs in a staff fraud. It then utilised a twin-track approach of a survey and interviews. A survey was distributed using a number of methods yielding 28 usable cases. Interviews were also sought with organisations willing to discuss staff fraud, which secured a further 17 cases. Both the survey and interview used the same questionnaire, although the latter enabled a deeper questioning of participants. Findings – This study examined 45 cases of staff fraud from a wide range of sectors drawn predominantly from larger organisations. From each of these cases detailed, estimates of the costs of dealing with the fraud were identified. Major additional costs included the costs of investigation, staff suspensions, internal disciplinary costs, external sanctions, permanent staff replacement, miscellaneous costs as well as intangible costs. The findings identified significant costs which are significantly above the initial value of the fraud, particularly on initial frauds under £25, 000. Research limitations/implications – Staff fraud is a very sensitive subject with many organisations unwilling to reveal what happens when it occurs. The approach was therefore to secure as much data as possible and as such this might not be representative of the broader economy. Practical implications – The paper highlights the need for greater investment in prevention given the substantial costs of staff fraud to deal with. Originality/value – This is the first attempt to gauge the full costs of staff fraud to an organisation.